Seasonal Groundwater Recharge Characterization Using Time-Lapse Electrical Resistivity Tomography in the Thepkasattri Watershed on Phuket Island, Thailand - Yacob T. Tesfaldet (Hydrology, 2019)
Understanding the recharge mechanisms in the vadose zone is crucial to groundwater management and artificial recharge development. In this study, a systematic characterization of seasonal groundwater recharge was done using time-lapse electrical resistivity tomography (time-lapse ERT). The objective of this study was to characterize the seasonal groundwater recharge through the vadose zone and streams. A total of six electrical resistivity surveys in two locations were taken during the dry and rainy seasons using an advanced geosciences incorporated (AGI) SuperSting R2 resistivity meter in 2018. Then, time-lapse inversion was calculated using the dry season ERT as the base model and the rainy season ERTs as the monitoring datasets. The results showed a significant decrease in inverted resistivity from the dry season to the rainy season, which suggests rainwater infiltration through the vadose zone. Similarly, significant water level rise was observed in wells monitored during the survey indicating groundwater recharge. The time-lapse ERT showed, in one case, the Nang Dak stream and the unsaturated zones are the preferential groundwater recharge zones throughout the year; in another case, the Rieng stream is the groundwater discharge zone and the vadose zone is the preferential recharge zone. Finally, a simplified conceptual hydrogeological model representing the study area is presented to visualize the recharge mechanisms in the study area.